ANALYSIS OF ENTREPRENEURIAL INTEREST IN BATIK PRODUCTS FOR STUDENTS IN THE PERSPECTIVE OF SELF EFFICACY, SOCIAL CAPITAL AND ENTREPRENEURIAL LITERACY - Kusuma Wardhani, Nia; Siregar , Edi; Nashar, Muhammad; Bahat Nauli, Sukarno (Dinasti International Journal of Management Science, 2020)
The limited employment resulted in the emergence of educated unemployment because the absorption of tertiary graduates in the labor market is also limited. Based on BPS data in 2019, Micro Small Medium Enterprise absorbs 97% of the national workforce. This study aims to analyze the entrepreneurial interest in batik products among college students from the perspective of self-efficacy, social capital, and entrepreneurial literacy. This research is a quantitative study using Path Analysis method. The results of this study are there is an effect of self-efficacy on entrepreneurial literacy, there is an effect of social capital on entrepreneurial literacy, there is an effect of self-efficacy on entrepreneurial interest in batik products, there is an effect of social capital on entrepreneurial interest in batik products, there is an effect of entrepreneurial interest in batik products. The results of this study are expected to increase entrepreneurial interest among students by applying various factors that influence it.